A Malignant Mass in Rectum : a Complication of Familial Adenomatous Polyposis - Joshi, B.R. (Nepalese Journal of Radiology, 2017)
An unusual case of multiple round filling defects in colon in a patient with family history of rectal malignancy and its pathogenesis has been described. Family history may not be present in 25%. Usually there is family history of polyp or colorectal carcinoma at 40 years or younger. The young patient may suffer from unexplained rectal bleeding, diarrhea, abdominal pain. Some may be asymptomatic until they develop carcinoma. Nepal Journal of Radiology Vol.5(1-2) 2015: 21-25